2017
DOI: 10.1038/s41598-017-12010-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved analysis of DNA-protein interactions in living cells by UV laser pulses

Abstract: Interactions between DNA and proteins are mainly studied through chemical procedures involving bi-functional reagents, mostly formaldehyde. Chromatin immunoprecipitation is used to identify the binding between transcription factors (TFs) and chromatin, and to evaluate the occurrence and impact of histone/DNA modifications. The current bottleneck in probing DNA-protein interactions using these approaches is caused by the fact that chemical crosslinkers do not discriminate direct and indirect bindings or short-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Together, these observations support the claim that DarT Mtb primarily exerts its toxicity by ADP-ribosylation of DNA (Jankevicius et al, 2016). In addition, DarG Mtb forms cytosolic complexes with several proteins involved in DNA repair, either in a direct or indirect manner (Figure 2a-b , S4), it is possible that these interactions are too transient or weak to be detected (Nebbioso et al, 2017). Alternatively, the binding of DarG Mtb to DNA may lack sequence specificity, which would preclude detection of enriched peaks at a population level.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Together, these observations support the claim that DarT Mtb primarily exerts its toxicity by ADP-ribosylation of DNA (Jankevicius et al, 2016). In addition, DarG Mtb forms cytosolic complexes with several proteins involved in DNA repair, either in a direct or indirect manner (Figure 2a-b , S4), it is possible that these interactions are too transient or weak to be detected (Nebbioso et al, 2017). Alternatively, the binding of DarG Mtb to DNA may lack sequence specificity, which would preclude detection of enriched peaks at a population level.…”
Section: Discussionsupporting
confidence: 78%
“…This implies that the complex of DarG Mtb with DNA‐repair proteins is poised to be recruited to sites of DNA‐ADP‐ribosylation (Figure 2b, Model VI), where it mediates removal of the ADPr moiety followed by correction of the associated DNA damage. While we failed to detect DarG Mtb bound to DNA, including under conditions that induced ADP‐ribosylation (Figures 2c, ), it is possible that these interactions are too transient or weak to be detected (Nebbioso et al ., 2017). Alternatively, the binding of DarG Mtb to DNA may lack sequence specificity, which would preclude detection of enriched peaks at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…The application of single-cell transcriptomics is likely to unveil the variability and heterogeneity of cancer cells and of “normal cells” positioned in cancer tissue and premalignant lesions. Assays devoted to decrypting dynamics and temporal resolution [ 24 , 25 ] might also explain whether and which stochastic epigenetic deregulations in cells represent an early indicator of tumor aggressiveness and to what extent transition states and rapid changes play a role. Similarly, new 3D models of tumorigenesis, such as organoids and spherical models, will be required to clarify the potential molecular relationship between tumor cells, microenvironment, and position of cancer cells within the tissue, since current models are based on the paradigm that cancer is a genetic disease.…”
Section: Altered Epigenetic Landscapes: Consequence or Hallmark(s) Ofmentioning
confidence: 99%
“…High-intensity femtosecond lasers provide a plethora of applications reaching from ultrafine material processing 45 , highprecision medical surgery 46 , to the detection of biomolecular processes 47 . In the search for effective cross-linking methods of proteins and DNA, we and others have previously shown that femtosecond lasers are promising for this purpose because they provide high cross-linking yields while minimizing DNA damage 20,24,48,49 . With recent advances in XL-MS in the sample preparation, MS instrumentation, and bioinformatics side 17,50 , we here combined this highly effective cross-linking strategy with an optimized purification protocol for cross-linked peptides, and MS-based read out of protein-DNA cross-links.…”
Section: Discussionmentioning
confidence: 99%
“…This is largely due to the fact that double-stranded oligonucleotides are about an order of magnitude less efficiently cross-linked by UV than single-stranded oligonucleotides 18 . Yet, over the last three decades a small number of studies have shown that the efficiency of protein-DNA cross-linking can be increased by using UV lasers [19][20][21][22][23][24] . For a given total energy, the efficiency of protein-DNA cross-linking was shown to largely depend on the length of the laser pulses.…”
mentioning
confidence: 99%